Microscale evaluation of epoxy matrix composites containing thermoplastic healing agent - Guerra, Érick Stéfano Silveira (2022)
Epoxy matrix composites are often subjected to adverse service conditions leading to the formation of microcracks. Microcracks are of great concern because they can act as nucleation sites for more prejudicial types of damage, such as delamination. Among the solutions to mitigate the deleterious effect of matrix microcracking is the use of thermoplastic healing agents. Poly(ethyleneco-methacrylic acid) (EMAA) has been particularly used as a thermoplastic healing agent because of its suitable chemical and physical properties. When the material is heated, the thermoplastic phase dispersed in the epoxy matrix is allowed to flow into microcracks and restore mechanical properties. The addition of EMAA particles, however, may alter chemical and thermomechanical properties of epoxy composites. These changes may also affect other fundamental features of epoxy composites, such as their fiber-matrix interfacial properties. Therefore, the objectives of this work are: (1) study the effects of EMAA addition on epoxy formation, (2) investigate the effect of EMAA addition on fiber-matrix interfacial properties, and (3) study the potential for self-healing through micromechanical testing. The effect of a 10 wt.% EMAA modified epoxy was investigated through infrared spectroscopy and differential scanning calorimetry (DSC) experiments. The results suggested that EMAA addition may cause changes during the epoxy network formation. Then, single fiber pull-out tests were used to characterize the fiber interfacial shear strength (IFSS) of pure and modified epoxy systems, as well as between fiber and pure EMAA. IFSS results of pure and modified epoxy were quite similar, revealing that epoxy modification did not significantly alter fiber-matrix interfacial properties. On the other hand, IFSS measurements of fiber-EMAA presented considerably lower values than fiber-epoxy, suggesting that healing is most likely held by fiber-epoxy or EMAAepoxy interactions. A novel method to assess the healing efficiency (η) using optically monitored single fiber pull-out testing was proposed. According to the data obtained, healing efficiency of EMAA modified epoxy was lower than that of pure epoxy systems. The attenuated matrix shrinkage effect due to the addition of rubbery EMAA particles, along with the lower IFSS results of EMAAfiber are proposed to explain the observed low η values. Complementary tests investigated thermomechanical properties and the curing of the EMAA modified epoxy, along with the effect of healing on the chemical structure and its IFSS properties.